Wandering Gastrostomy - Kamalesh, Naduthottam Palaniswami (Indian J Surg, 2015)
Percutaneous endoscopic gastrostomy (PEG) is a relatively safe and effective method of providing nutrition to patients with neurologic deficits or proximal gastrointestinal pathology. Complications that follow this common procedure include dislodgement, dysfunction, infection, gastric/colonic perforation, bleeding, peritonitis, or death. The emergency physician should be aware of the complications and symptoms/signs associated for appropriate management of these patients. We present a case of a young lady who developed a cerebral infarction following amniotic fluid embolism during her cesarean section and had undergone a PEG tube placement. She developed displacement of this PEG tube and underwent another PEG tube placement. She later presented to us with PEG tube migration into the transverse colon and required surgical removal of the same PEG tube.